EFEKTIFITAS PEMBERIAN AIR REBUSAN JAHE DALAM MENGURANGI EMESIS GRAVIDARUM PADA IBUHAMIL TRIMESTER 1 DAN 2 DI KLINIK SETIA BUDI BIDAN LISDA WATI - Sri Juliani; Elvi Era Liesmayani; Noviwati Nanda Tanjung (Jurnal Maternitas Kebidanan, 2022)
Pregnancy is the most beautiful gift that many women dream of, a desired or uncertain pregnancy will be dispensed with, including the nausea and vomiting that pregnant women often feel. Nausea and vomiting in pregnant women is a physiological condition experienced by every first trimester pregnant woman when excessive nausea and vomiting (hypermesis) affects the mother and her fetus. World Health Organization (WHO) In 2016 almost 830 women die every day related to pregnancy and childbirth, 99% of all maternal deaths occur in developing countries. This study aims to determine the effectiveness of giving ginger boiled water in reducing emesis gravidarum in pregnant women in the 1st and 2nd trimesters at the Setia Budi Bidan Lisda Wati Clinic in 2022. The design of this study was a Quasy Experiment with a One Group Pre Test – Post test Design. The population in this study were 10 people. The sampling technique used purposive sampling technique is a sample selection based on certain criteria as many as 10 people, the statistical test used is the t test. The data obtained were the pre-test before being given a value of 10 SD 1.581 while the post-test after being given N10 SD 1.955. from the results of the statistical test, namely the t test with a confidence level of 95%, it is known that the P-value = 0.000 <0.05. The conclusion in this study is the effectiveness of giving ginger boiled water in reducing emesis gravidarum in pregnant women in the 1st and 2nd trimester at the Setia Budi Bidan Lisda Wati Medan clinic in 2022. It is suggested that the results of this study can be applied to reduce emesis in pregnant women in a natural way, namely drinking ginger decoction..